Physiopathology and treatment of critical bleeding: a literature review - Celia González-Guerrero; José Bruno Montoro-Ronsano (Farmacia Hospitalaria)
Objectives: to develop the different factors involved in the physiopathology of trauma-induced coagulopathy, through a review of publications on the matter; as well as to assess the evidence available on the treatment of critical bleeding and the recommendations by clinical practice guidelines. Methods: a search has been conducted on the bibliography published about the physiopathology and treatment of critical bleeding in the PUBMED, BestPractice, UpToDate databases and the Cochrane Plus Library. The main key words used for this search were “early trauma induced coagulopathy”, “mechanisms of early trauma-induced coagulopathy”, “blood transfusion guidelines”, “massive transfusion guidelines” and ”fibrinogen replacement therapy”. The most clinically relevant articles were selected for this review. Conclusions: the physiopathology of the trauma-induced coagulopathy is a more complex matter and involves more factors than was initially assumed. The early treatment of the coagulopathy is critical for the initial management of the critical bleeding. However, the use of blood derivatives should be rational and based on homogeneous and high-quality scientific evidence. The main cornerstones for the treatment of critical bleeding are: fluid therapy, fibrinogen concentrate, prothrombin complex concentrate, plasma, erythrocyte or platelet concentrates, tranexamic acid, and calcium. Their administration should be assessed depending on the clinical condition of each patient.